Pengembangan Ensiklopedia Etnobotani Peralatan Rumah Tangga di Kabupaten Sambas Sebagai Sumber Pembelajaran Biologi - Kessi Hafsah; Mahwar Qurbaniah; Hanum Mukti Rahayu (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an ethnobotanical encyclopedia of traditional household utensils in Sambas Regency as a local wisdom-based biology learning resource. The research used a modified Research and Development (R&D) 4D model—Define, Design, Develop—excluding the Disseminate stage. Data were collected through observation, interviews, documentation, student response questionnaires, expert validation, and development trials. The findings revealed 15 plant species from 13 families commonly used by the local community, such as bamboo and rattan, for making traditional household items. The encyclopedia was developed based on ethnobotanical identification, plant classification, morphology, and usage. Created using Canva, the encyclopedia was validated by material, media, and language experts and tested on Grade X students at MAN 1 Sambas. Validation results showed very high scores from material experts (92.19%) and media experts (84.33%), and valid results from language experts (77.78%). Student response trials showed good results at both small-scale (61.02%) and large-scale (73.10%) levels. In conclusion, the developed encyclopedia is suitable for use as a local wisdom-integrated biology learning resource.